NATURE OF SCIENCE IN THE TEACHING MATERIALS ABOUT CHEMISTRY OF THE RARE EARTH ELEMENTS: RESULTS FROM A QUALITATIVE CONTENT ANALYSIS STUDY - UMAR, RISNAWATI; MUDZAKIR, AHMAD (LPPM Universitas Banda Naira, 2025)
Understanding nature of science (NOS) is part of developing scientific literacy skills. There are seven aspects of NOS that are included; tentative, subjectivity, empirical, creative and imaginative, sociocultural, diverse research methods and relationship between scientific theory & law. The purpose of this research is to gain the concept maps and teaching-learning sequences (TLS) from the views of scientists regarding to understanding of NOS on rare earth elements (REE) through Education for Sustainable Development (ESD) approach. The qualitative content analysis method was chosen in this study throughout the literature analysis based on books sources, review articles and research articles. The instrument avail of in this study was a content analysis format, which was portray descriptively to construct the understanding NOS of prospective chemistry teacher students. The outcome of the analysis are compiled in the form of concept maps and TLS with triangulation between researchers as a guarantee of validity. The results of the concept map and TLS that have been compiled show the relationship between the seven aspects of NOS which are integrated into REE learning materials. REE is known have unique properties based on the electron configuration but is increasingly difficult to find in nature, thus encouraging creativity to create renewable energy that can be recycled from electronic waste. The outcomes of this REE and NOS concept map and TLS are expected to be used to develop the design of REE teaching materials and didactic designs that are oriented ESD.